2023
DOI: 10.1111/iwj.14557
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the efficacy, safety and satisfaction of regenerative medicine treatments, including platelet‐rich plasma, stromal vascular fraction and stem cell‐conditioned medium for hypertrophic scars and keloids

Alireza Jafarzadeh,
Arash PourMohammad,
Azadeh Goodarzi

Abstract: The primary objective of this study is to examine the efficiency of various regenerative medicine approaches, such as platelet‐rich plasma, cell therapy, stromal vascular fraction, exosomes and stem cell‐conditioned medium, in the process of healing hypertrophic and keloid scars. Major databases including PubMed, Scopus and Web of Science were systematically searched, and based on the content of the articles and the inclusion and exclusion criteria, eight articles were selected. Out of these eight articles, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…One potential way PRP aids in healing inflammatory skin lesions is by releasing a variety of growth factors, such as platelet-derived growth factor (PDGF) and TGF-β, from alpha platelet granules. This increase in TGF-β levels can then trigger negative feedback within the signaling pathways involved in inflammation [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One potential way PRP aids in healing inflammatory skin lesions is by releasing a variety of growth factors, such as platelet-derived growth factor (PDGF) and TGF-β, from alpha platelet granules. This increase in TGF-β levels can then trigger negative feedback within the signaling pathways involved in inflammation [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regenerative medicine is a crucial field of medicine known for its effectiveness in treating numerous inflammatory and degenerative diseases. This treatment approach encompasses various methods such as platelet-rich plasma (PRP), stromal vascular fraction (SVF), conditioned media, and the transplantation of autologous epidermal melanocyte/keratinocyte cells [ 1 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their beneficial potential rests on the ability to deliver a high concentration of growth factors to the target tissues [356]. In addition, platelets are important donors of mitochondria, and platelet-derived mitochondria can promote wound healing by reducing apoptosis caused by oxidative stress in vascular endothelial cells [357]. The efficiency of various regenerative medicine approaches, such as platelet-rich plasma, cell therapy, stromal vascular fraction, exosomes and stem cell-conditioned medium, are continually emerging with a focus on personalized, patient-specific treatments, and it is reported that regenerative medicine is an effective method with minimal side effects that can be used in the treatment of HTSs and KDs [353,[358][359][360].…”
Section: Dexamethasone (Dex)mentioning
confidence: 99%
“…Research has shown that it can effectively treat a number of problems, including alopecia, acne, melasma, burn scars, and skin hyperpigmentation [9]. Many over-the-counter and prescription topical treatments are available that promise to reduce discomfort, enhance the look of scars, and speed the healing process of wounds.…”
Section: Introductionmentioning
confidence: 99%